An Islamic Ethnomethodology Approach to Examine Mosque Accounting Practices - Thalib, Mohamad Anwar (Institut Agama Islam Negeri Ponorogo, 2023)
This study utilizes an Islamic paradigm with an Islamic ethnomethodology approach to investigate mosque accounting practices. The study uses both primary data, obtained through interviews and observations, and secondary data, which consists of documentation of mosque financial information records in books and on information boards. The data is analyzed through five stages: charity, knowledge, faith, revelation information, and good deeds, and collected through interviews, observation, and documentation. The study results show that mosque accounting practices are based on three main values: sincerity, responsibility, and trustworthiness. First, capital and cost accounting are practiced based on sincerity, which is reflected through the voluntary donations of funds by donors for the prosperity of the masjid, and the optimal work of administrators who do not receive a salary. Second, a simple accounting recording method is used, requiring a sense of responsibility, which is reflected through detailed financial records in album booklets and on bulletin boards. Third, accountability for incoming and outgoing funds is conditional on maintaining the congregation's trust, which is reflected in the expressions of the informants who stated that financial responsibility is their effort to maintain donors' trust. The implication of this research is to present the concept of mosque accounting practices based on the values of faith and fear of God. It concludes that mosque accounting is not only about material (money) but also about a sense of faith in the creator. Further research can study mosque accounting using other social theoretical approaches, such as Islamic phenomenology.